2020
DOI: 10.47626/1679-4435-2020-608
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal pain and ergonomic risks in teachers of a federal institution

Abstract: Introduction: Ergonomic risks are a major health hazard for teachers, causing musculoskeletal pain and decreasing both their quality of life and the quality of the education offered to students. Objectives: To evaluate musculoskeletal pain and ergonomic risk factors in the workplace of teachers at the São Bento do Sul Campus of the Instituto Federal Catarinense. Methods: Twenty-five teachers completed sociodemographic and ergonomic risk quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 24 publications
(28 reference statements)
1
10
1
4
Order By: Relevance
“…The study results showed that lifetime prevalence among teachers was 96.5%, the 7 day prevalence was 35.3%, and point prevalence was 24.7%. Other studies reported a lifetime prevalence of LBP from 34.8 to 48.1% [ 3 , 8 , 9 , 10 , 11 ], and 1 year prevalence from 45.6 to 64.9% [ 4 , 6 , 7 ]. These differences in the percentages may be due to the strategy for extracting data and the methodology used, sample age, sample size, the definition of LBP, or geographical factors [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The study results showed that lifetime prevalence among teachers was 96.5%, the 7 day prevalence was 35.3%, and point prevalence was 24.7%. Other studies reported a lifetime prevalence of LBP from 34.8 to 48.1% [ 3 , 8 , 9 , 10 , 11 ], and 1 year prevalence from 45.6 to 64.9% [ 4 , 6 , 7 ]. These differences in the percentages may be due to the strategy for extracting data and the methodology used, sample age, sample size, the definition of LBP, or geographical factors [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, there is only one study that analyses the knowledge of teachers in relation to postural education, but this study uses a non-validated questionnaire. In that study, 8% of participants reported no knowledge of ergonomics principles, while 72% reported some knowledge, 16% had a reasonable amount of knowledge, and 4% reported extensive knowledge [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Karaemer 18 , in 2020, evaluated musculoskeletal pain and ergonomic risk factors in the workplace of teachers at the São Bento do Sul Campus of the Institution Federal Catarinense. Results shows the main ergonomic risks to which teachers exposed were prolonged sitting and standing, sharp corners on desks, use of laptop touchpads and inadequate monitor height.…”
Section: Discussionmentioning
confidence: 99%
“…Elsődlegesen azonosított kockázati tényezőnek számít a tanári pályán eltöltött idő (Ojukwu et al, 2021;Kebede et al, 2019;Mohseni Bandpei et al, 2014;Erick & Smith, 2011), az életkor (Ojukwu et al, 2021;Amit & Malabarbas, 2020;Ceballos & Santos, 2015;Mohseni Bandpei et al, 2014), a női nem (Althomali et al, 2021;Elias et al, 2019;Kebede et al, 2019;Ceballos & Santos, 2015;Karakaya et al, 2015;Erick & Smith, 2011), a magasabb testtömegindex (Vega-Fernández et al, 2021;Kraemer, Moreira & Guimarães, 2020;Mohseni Bandpei et al, 2014), a dohányzás (Althomali et al, 2021), az alacsonyabb fizetési csoportba való tartozás (Amit & Malabarbas, 2020), a munkahelyi pszichoszociális tényezők (Elias et al, 2019;Zamri et al, 2017;Ceballos & Santos, 2015;Mohseni Bandpei et al, 2014) és az alacsony vezetői támogatás (Elias et al, 2019). A mozgásszervi elváltozások a testi panaszok megjelenése mellett negatív hatást gyakorolnak az életminőségre (Vega-Fernández et al, 2021), illetve kedvezőtlenül befolyásolják az általános egészségérzetet (Karakaya et al, 2015;Dilek & Ilker, 2012), a mentális egészséget (Vega-Fernández et al, 2021;Ceballos & Santos, 2015), továbbá együttjárást mutatnak a szorongással (Zamri et al, 2017), a depresszióval (Dilek & Ilker, 2012) és az alvászavarral (Kebede et al, 2019).…”
Section: Bevezetésunclassified